Development of a generic zebrafish embryo PBPK model and application to the developmental toxicity assessment of valproic acid analogs - Siméon, Ségolène; Brotzmann, Katharina; Fisher, Ciaran; Gardner, Iain; Silvester, Steve; Maclennan, Richard; Walker, Paul; Braunbeck, Thomas; Bois, Frederic Y. (Reproductive toxicology, 2020)
In order to better explain, predict, or extrapolate to humans the developmental toxicity effects of chemicals to zebrafish (Danio rerio) embryos, we developed a physiologically-based pharmacokinetic (PBPK) model designed to predict organ concentrations of neutral or ionizable chemicals, up to 120 h post-fertilization. Chemicals’ distribution is modeled in the cells, lysosomes, and mitochondria of ten organs of the embryo. The model’s partition coefficients are calculated with sub-models using physicochemical properties of the chemicals of interest. The model accounts for organ growth and changes in metabolic clearance with time. We compared ab initio model predictions to data obtained on culture medium and embryo concentrations of valproic acid (VPA) and nine analogs during continuous dosing under the OECD test guideline 236. We further improved the predictions by estimating metabolic clearance and partition coefficients from the data by Bayesian calibration. We also assessed the performance of the model at reproducing data published by Brox et al. (2016) on VPA and 16 other chemicals. We finally compared dose-response relationships calculated for mortality and malformations on the basis of predicted whole embryo concentrations versus those based on nominal water concentrations. The use of target organ concentrations substantially shifted the magnitude of dose-response parameters and the relative toxicity ranking of chemicals studied.
Gesehen am 13.05.2020